2022
DOI: 10.1177/20543581221107751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Donation Physicians on Deceased Organ Donation: A Systematic Review

Abstract: Background: An emerging strategy to increase deceased organ donation is to use dedicated donation physicians to champion organ donation. We sought to conduct a systematic review of the effectiveness of donation physicians in improving organ donation outcomes. Objective: A systematic review was conducted following Cochrane principles. MEDLINE, Embase, and CINHAL databases were searched from inception to March 26, 2020. Methods: Quantitative studies examining the effects of donation physicians on all deceased or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“… 27 , 28 , 29 Similarly, a recent systematic review reported that the engagement of donation physicians has the potential to significantly improve deceased donation. 30 The acceptance of donor coordinators reflects a culture change that has been enabled by the critical care leadership of our OPO and the implementation of Canadian best practices for organ donation. 31 , 32 The high consent rate is consistent with survey data that 81% of Canadians support organ donation.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 , 29 Similarly, a recent systematic review reported that the engagement of donation physicians has the potential to significantly improve deceased donation. 30 The acceptance of donor coordinators reflects a culture change that has been enabled by the critical care leadership of our OPO and the implementation of Canadian best practices for organ donation. 31 , 32 The high consent rate is consistent with survey data that 81% of Canadians support organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigaciones y revisiones en este campo enfatizan la importancia del personal médico especializado en donación de órganos, ya que la educación y el entrenamiento específico han demostrado aumentar la probabilidad de obtener el consentimiento familiar [9].…”
Section: Introductionunclassified